COMPLIANCE AUDIT OF STANDARD OPERATIONAL PROCEDURES (SOP) FOR PURCHASING OF MERCHANDISE INVENTORY AT PT TRINITI PERKASA INTERNASIONAL - Ananda, Silvia; Irsutami (Jurnal Bisnis Mahasiswa, 2022)
The purpose of this research was to determine the compliance level of employee with the Standard Operating Procedure (SOP) for purchasing merchandise at PT Triniti Perkasa Internasional. The data collection method used interviews based on the Internal Control Questionnaires (ICQ) then continued with observation and inspection for the implementation of tests based on the control testing program, while the analytical method used was descriptive. The results showed that the compliance level of employee was 66.14%. The recommended recommendations are simplification of SOP, improvement of document design, and improvement of archival management.